Static modelling of the material flows of micro- and nanoplastic particles caused by the use of vehicle tyres. (1st December 2021) - Prenner, Stefanie; Allesch, Astrid; Staudner, Margarethe; Rexeis, Martin; Schwingshackl, Michael; Huber-Humer, Marion; Part, Florian
Abstract: The emissions of tyre wear particles (TWPs) into the environment are increasing and have negative impacts on the environment and human health. The aim of this study was therefore to establish a mass balance for vehicle tyres und TWP emissions in Austria using static material flow analysis, which enabled a quantification of mass flows of rubber including carbon black as the most mass-relevant tyre filler. Vehicle-specific and mileage-dependent emission factors were used to calculate the TWP emissions. The results for the year 2018 indicate that 80% of the tyre rubber remained in use, while 14% was re-treaded, recycled, incinerated or exported as end-of-life tyres and 6% was emitted as TWPs to air, soil or surface water. Of these 21, 200 t/y released and dissipative lost TWPs, 6% were microscale, with a possible size between 0.1 and 10 μm, and 0.3% were nanoscale below 0.1 μm. The mass balance on the substance level shows that the TWPs contained 5, 500 t/y of carbon black emitted in the form of airborne TWPs (6%) or entering in the soil or surface waters (47% each). Regarding air pollution from road vehicles, about 3, 600 t/y were non-exhaust emissions, including tyre, brake and road-surface wear, which contributed to 9% of total dust emissions across Austria. Scenario analysis for 2050 with regard to e-mobility and the European Green Deal reveals that non-exhaust emissions can only be significantly reduced by a general reduction of the mileage or an environmentally friendly tyre design. This modelling approach provides a solid basis for decision makers in traffic planning as well as for chemical risk assessment. However, dynamic models with higher temporal and spatial resolution are needed to predict future mass flows of TWPs and their environmental fate, including their degradation products and possible accumulation effects. Graphical abstract: Image 1 Highlights: Static material flow analysis for vehicle tyres in Austria (2018) was conducted. Ca. 80% of tyre rubber remains in use, 14% are disposed and 6% are emitted. In total, 2.4 kg/cap.y tyre wear particles are emitted (6% micro-, 0.3% nanoscale). Ca. 9% of the total suspended particles are non-exhaust traffic emissions. Shift to e-vehicles leads to a further increase of non-exhaust emissions in 2050.